2021
DOI: 10.1002/biof.1780
|View full text |Cite
|
Sign up to set email alerts
|

Golgi stress response: A regulatory mechanism of Golgi function

Abstract: The organelle of eukaryotes is a finely regulated system. Once disturbed, it activates the specific autoregulatory systems, namely, organelle autoregulation.Among which, the Golgi stress response accounts for one. When the abundance and capacity of the Golgi apparatus are insufficient compared with cellular demand, the Golgi stress response is activated to enhance the function of the Golgi apparatus. Although the molecular mechanism of the Golgi stress response has not been well characterized yet, it seems to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 94 publications
(91 reference statements)
0
15
0
Order By: Relevance
“…The Golgi apparatus may also sense and transduce stress signals to maintain homeostasis of the organelle [39,45]. Under Golgi stress conditions, the transcription of Golgi-related genes is upregulated to restore Golgi function [49][50][51]77]. Taniguchi et al [50] reported that the TFE3 transcription factor plays an important role in the expression of Golgi-related genes in response to Golgi stress.…”
Section: Discussionmentioning
confidence: 99%
“…The Golgi apparatus may also sense and transduce stress signals to maintain homeostasis of the organelle [39,45]. Under Golgi stress conditions, the transcription of Golgi-related genes is upregulated to restore Golgi function [49][50][51]77]. Taniguchi et al [50] reported that the TFE3 transcription factor plays an important role in the expression of Golgi-related genes in response to Golgi stress.…”
Section: Discussionmentioning
confidence: 99%
“…The Golgi stress response is a relatively recently proposed stress signal that is less well understood than ER stress, which is caused by dysfunction of the nearby organelle, the ER [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Until now, Golgi stress has been classified by several signaling pathways, including TFE3, CREB3, and Hsp47 [ 15 , 16 , 17 ]; however, there remain many unresolved issues, such as the endogenous stimuli that cause Golgi stress and the downstream factors of these stress sensors. We previously characterized the processing and degradation of CREB3 in a mouse neuroblastoma cell line, Neuro2a [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the concept of the Golgi stress response remains obscure. Even under such circumstances, TFE3, CREB3, and Hsp47 have been reported as factors involved in Golgi stress [ 15 , 16 , 17 ]. Several TFE3 target genes (e.g., GM130 and SIAT4A), and an Arf4 gene as a target factor for CREB3, have been reported [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, this response involves the activation of the TFE3, heat shock protein 47 (HSP 47), CREB3, E26 transformation specific (ETS), proteoglycan, and mucin pathways. The CREB3 and ETS pathways, for example, can promote apoptosis [ 121 ]. Golgi stress inducers caused ferroptosis in HeLa cells, which can be prevented through SLC7A11 or GPX4 overexpression, as well as ACSL4 depletion [ 122 ].…”
Section: Role Of Different Organelles In Apoptosis and Ferroptosismentioning
confidence: 99%